Vascular malformation and their unpredictable evolution: A true challenge for physicians: A deeper insight into vascular malformations. - Della Rosa, Norman; Bertozzi, Nicolò; Adani, Roberto (Acta Biomedica Atenei Parmensis, 2020)
Vascular anomalies are mainly divided into two groups: vasoproliferative/vascular neoplasms (e.g., hemangioma), and vascular malformations (VMs). The main difference between the two resides in the histopathological assessment, while vascular tumors are true neoplasm, typically congenital with rapid postnatal growth, and eventual slow regression; VMs have a single endothelial cell lining, tend to be regarded as acquired despite being congenital in nature, can undergo sudden and massive growth, miming neoplastic proliferation. Arteriovenous malformation (AVMs) are one type of fast flow VMs, with a four-stage natural history, and potentially disruptive evolution. Magnetic resonance is the gold-standard for diagnosis and pre-operative planning while computer tomography is particularly valuable for AVMs involving bones, and selective angiography can define source / draining vessels for sclerotherapy and surgical planning. Given their unpredictable evolution, AVMs shouldn’t be treated until symptomatic, complicated, or aesthetically unacceptable. Surgical resection should be preceded by arterial embolization from 24 to 72 hours, which must be extensive in order to reduce the risk of recurrence. Pain due to ischemic condition is one of the most common and debilitating symptoms of AVM, while gassosus gangrene is the most feared complication as they can become pabulum for bacteria overgrowth eventually resulting in necrotizing fasciitis. Given their clinical evolution, VMs pose physicians at great challenge in identifying the best-suited treatment for each case. It is of paramount importance to be able to make accurate diagnosis, understand the basic physiology, and use appropriate diagnostic and treatment modalities to optimize outcome. Proper multidisciplinary approach along with constant psychological support is the basis for a successful final outcome. Aim of this work was to provide a deeper insight into these relatively uncommon pathology and related hardship that afflicts both patients and their families.